Hip Circumference is an Important Predictor of Plasma C-reactive Protein Levels in Overweight and Obese Taiwanese Women - Hei-Jen Jou; I-Ping Hsu; Pei-Ying Ling; Chia-Tzu Lin; Suei-Tsau Tsai; Hui-Ting Huang; Shiao-Chi Wu (Elsevier, 2006)
Objective: To investigate the relationship between serum levels of C-reactive protein (CRP) with obesity, insulin resistance and metabolic syndrome in overweight or obese Taiwanese women. Materials and Methods: Analysis was performed on data from 59 overweight or obese women enrolled in a cross-sectional study. Pearson's correlation coefficients were determined between CRP and simple anthropometric indices, fasting insulin, homeostasis model assessment (HOMA) and serum lipid levels. Forward stepwise regression procedure was used to find a "best" subset of predictor variables for CRP. Results: CRP was found to have significantly positive correlation with body weight, waist circumference, hip circumference, body mass index, log of fasting glucose levels, fasting insulin levels and HOMA. Forward stepwise regression procedure showed that the best predictor for CRP was hip circumference. Conclusion: The correlation between CRP and insulin resistance or abnormal lipid levels is attributed to their strong correlations with obesity.